Can fixation instability improve text perception during eccentric fixation in patients with central scotomas?. Issue 4 (18th March 2004) - Déruaz, A; Matter, M; Whatham, A R; Goldschmidt, M; Duret, F; Issenhuth, M; Safran, A B
Abstract : Background: Oculomotor behaviour was investigated in 14 patients with central scotomas from age related macular degeneration (AMD) or Stargardt's disease. A scanning laser ophthalmoscope (SLO) was used to project letters and words onto the retina and to assess fixation behaviour. Five patients reported while deciphering letters that they needed to "move their eye" to prevent the image from vanishing. The observation of the SLO fundus images revealed that the gradual disappearance of the stimulus did not result from a transient projection of the word in the lesion. This prompted the authors to investigate, in an experimental setting, whether purposeful changes in fixation position could improve the perception of an eccentrically fixated text stimulus. Methods: Twenty normal subjects were asked to alternate fixation, every three to four seconds, between two vertically aligned dots, spaced 10° apart, and to report any changes in the perception of a laterally located letter, 1.5° in height, 7° apart and equidistant between the two fixation spots. Results: Nineteen subjects reported a transient refreshment of the letter image immediately after the realisation of a saccade. Improved perception lasted approximately a second. With persistent fixation, they noted a rapid fading effect that reduced letter recognition. Conclusion: These observations suggest that ocular instability during eccentric viewing can have a functional advantage, probably related to counteracting Troxler's phenomenon. In addition to alternating between PRLs, it appears that saccades related to fixation instability might be valuable and improve text perception in individuals with a central scotoma and eccentric fixation. This possibility should be taken into consideration when conducting visual rehabilitation procedures.